Management of pemphigus vulgaris: challenges and solutions - Gregoriou S; Efthymiou O; Stefanaki C; Rigopoulos D (Dove Medical Press, 2015)
Stamatis Gregoriou, Ourania Efthymiou, Christina Stefanaki, Dimitris Rigopoulos 2nd Department of Dermatology and Venereology, University of Athens Medical School, Attikon Hospital, Athens, Greece Abstract: The main objective in the treatment of pemphigus vulgaris is to control the disease, prevent relapses, and avoid adverse events associated with the prolonged use of steroids and immunosuppressive agents. Systemic corticosteroids remain the gold standard treatment for pemphigus vulgaris. Azathioprine and mycophenolate mofetil are the first line of steroid-sparing treatment. Rituximab is extremely effective in recalcitrant pemphigus, when other treatments fail to control the disease. The European Dermatology Forum recommends tapering prednisolone by 25% every 2 weeks after the consolidation phase, and a 5 mg reduction every 4 weeks when the dose is reduced to <20 mg. If the patient relapses, options include increasing steroids back to the previous dose, adding an immunosuppressant if using steroid monotherapy, or replacing a first-line immunosuppressant by another if already on combination therapy. Keywords: pemphigus vulgaris, treatment, steroids, rituximab, azathioprine, mycophenolate